Attention Dysregulation in Breast Cancer Patients Following a Complementary Alternative Treatment Routine: A Double-Blind Randomized Trial. (May 2021) - Dolev, Talya; Ben-David, Merav; Shahadi, Ilanit; Freed, Yaakov; Zubedat, Salman; Aga-Mizrachi, Shlomit; Brand, Zev; Galper, Shira; Jacobson, Galia; Avital, Avi
Introduction: Breast cancer patients and survivors frequently report fatigue, emotional, and cognitive disturbances, which reduce performance at all levels of occupation and make life quality issues a considerable clinical concern. The aim of this study is to evaluate attention and emotion regulation across radiotherapy period and the possible effects of complementary alternative medicine (CAM). Methods: Fifty-seven patients with unilateral breast cancer underwent surgery and systemic chemotherapy before participating in this double-blind randomized study. Two thirds were given CAM (n = 38) while the rest received placebo (carrier only, n = 19). Patients' attention and anxiety were physiologically tested at baseline, 2 and 4 weeks during the radiation period as well as 1-month after the end of radiation session. Results: Both groups showed similar levels of anxiety with no significant differences at baseline nor post-radiotherapy. Long-term significant recovery of attention performance was observed in the CAM patients, accompanied by a similar tendency in anxiety level, measured by the eye-blink probability. Conclusions: This study physiologically validates the attention impairment reported among breast cancer survivors; also, it depicted a beneficial late-effect of a routine CAM on attention dysregulation. The suggested non-invasive physiological measures can physiologically monitor patients' psychological and cognitive well-being as well as evaluate the beneficial effect of CAM in breast cancer patients by assessing their coping ability to support the treatment plan. Thus, the results have potential clinical implications on patients' and survivors' quality of life. Trial Registration: NIH, NCT02890316. Registered July 2016, http://www.ClinicalTrials.gov